If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 4) = 16 Reorder the terms: 3(4 + 2x) = 16 (4 * 3 + 2x * 3) = 16 (12 + 6x) = 16 Solving 12 + 6x = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 6x = 16 + -12 Combine like terms: 12 + -12 = 0 0 + 6x = 16 + -12 6x = 16 + -12 Combine like terms: 16 + -12 = 4 6x = 4 Divide each side by '6'. x = 0.6666666667 Simplifying x = 0.6666666667
| 12+5w=5(-w-8)-4(6w-2) | | 6(-7n-5)=306 | | -2x+5=4x+-13 | | 1-3m+4m=0 | | 17x/x+32x/x=100 | | 6x-4x+8-5= | | 2/3*4/12 | | -164=4(5v-1) | | 12+-5x=3x+-4 | | 5-(n+-4)=3(n+2) | | -8=m/3 | | 7x+3=5x+23 | | (6w+4v-5)(3W-4)= | | 1-1=1-1 | | 0.49(2s+4)=48 | | 17+x/x+32+x/x=100 | | 5(3r-8)=-85 | | 2+2(x+4)=4(2x+14) | | 1/7(x-7)+22=26 | | 5-9(3x+7)=8 | | 1k+12=-4 | | 10x-15x-114=86 | | 5(3x+4)=8 | | 1.3x+3.1=0 | | 12=7k-4k | | 6.5p-2.3=-8.8 | | b/2+1/5=19 | | 8-4x+4=-20 | | X+-7=5+-3x | | 96x/3=11x/4+6 | | x^4n-5x^2n+4=0 | | 11/10m+2=7/6m+4/3 |